Answer:
Factoring the expression
completely we get ![\mathbf{xy^4(x+1)(x^2-x+1)}](https://tex.z-dn.net/?f=%5Cmathbf%7Bxy%5E4%28x%2B1%29%28x%5E2-x%2B1%29%7D)
Step-by-step explanation:
We need to factor the expression
completely
We need to find common terms in the expression.
Looking at the expression, we get
is common in both terms, so we can write:
![xy^4+x^4y^4\\=xy^4(1+x^3)](https://tex.z-dn.net/?f=xy%5E4%2Bx%5E4y%5E4%5C%5C%3Dxy%5E4%281%2Bx%5E3%29)
So, taking out the common expression we get: ![xy^4(1+x^3)](https://tex.z-dn.net/?f=xy%5E4%281%2Bx%5E3%29)
Now, we can factor the term (1+x^3) or we can write (x^3+1) by using formula:
![a^3+b^3=(a+b)(a^2-ab+b^2)](https://tex.z-dn.net/?f=a%5E3%2Bb%5E3%3D%28a%2Bb%29%28a%5E2-ab%2Bb%5E2%29)
So, we get:
![xy^4(1+x^3)\\=xy^4(x^3+1)\\Applying\:the\:formula\;of\:a^3+b^3\\=xy^4(x+1)(x^2-x+1)](https://tex.z-dn.net/?f=xy%5E4%281%2Bx%5E3%29%5C%5C%3Dxy%5E4%28x%5E3%2B1%29%5C%5CApplying%5C%3Athe%5C%3Aformula%5C%3Bof%5C%3Aa%5E3%2Bb%5E3%5C%5C%3Dxy%5E4%28x%2B1%29%28x%5E2-x%2B1%29)
Therefor factoring the expression
completely we get ![\mathbf{xy^4(x+1)(x^2-x+1)}](https://tex.z-dn.net/?f=%5Cmathbf%7Bxy%5E4%28x%2B1%29%28x%5E2-x%2B1%29%7D)
Answer:
39
Step-by-step explanation:
Just add
Answer:
t
=
26
∘
57
+
k
360
∘
Step-by-step explanation:
tan
t
=
1
2
Calculator and unit circle give 2 solutions for (0, 360) -->
t
=
26
∘
57
, and
t
=
180
+
26.57
=
206
∘
57
General answer:
t
=
26
∘
57
+
k
360
∘
Answer:0.000810
Step-by-step explanation:
Given
A committee of 3 members is formed using
5 Admin, 34 teachers, and 4 staff
Favorable outcomes are selecting 3 members as Administrators
total members =5+34+4=43
Probability is given by
![\Rightarrow P=\dfrac{\text{Favorable}}{\text{Total}}](https://tex.z-dn.net/?f=%5CRightarrow%20P%3D%5Cdfrac%7B%5Ctext%7BFavorable%7D%7D%7B%5Ctext%7BTotal%7D%7D)
![\Rightarrow P=\dfrac{^5C_3}{^{43}C_3}=\dfrac{10}{43\times 41\times 7}\\\\\Rightarrow P=\dfrac{10}{12,341}=0.000810](https://tex.z-dn.net/?f=%5CRightarrow%20P%3D%5Cdfrac%7B%5E5C_3%7D%7B%5E%7B43%7DC_3%7D%3D%5Cdfrac%7B10%7D%7B43%5Ctimes%2041%5Ctimes%207%7D%5C%5C%5C%5C%5CRightarrow%20P%3D%5Cdfrac%7B10%7D%7B12%2C341%7D%3D0.000810)
Answer:
This is pythagoras
A squared plus b squared equals c squared.
The unknown side is c as its the hypotenuse,
So the length of the first side is 6.4 this squared = 40.96
The other length is 12 as 6 is the radius so the diameter of the circle amd therfore the length of the triangle is 12.
12 squared is 144
144 + 40.96 = 184.96
The length of c squared is 184.96
To find the length of c alone we calculate the square root.
The square root of 184.96 = 13.6
? = 13.6